The impact of phlebotomy in nonalcoholic fatty liver disease: A prospective, randomized, controlled trial - Adams, L.; Crawford, D.; Stuart, K.; House, M.; St Pierre, T.; Webb, M.; Ching, H.; Kava, J.; Bynevelt, M.; Macquillan, G.; Garas, G.; Ayonrinde, Oyekoya; et al. (John Wiley and Sons Inc., 2015)
Iron is implicated in the pathogenesis of liver injury and insulin resistance (IR) and thus phlebotomy has been proposed as a treatment for nonalcoholic fatty liver disease (NAFLD). We performed a prospective 6-month randomized, controlled trial examining the impact of phlebotomy on the background of lifestyle advice in patients with NAFLD. Primary endpoints were hepatic steatosis (HS; quantified by magnetic resonance imaging) and liver injury (determined by alanine aminotransaminase [ALT] and cytokeratin-18 [CK-18]). Secondary endpoints included insulin resistance measured by the insulin sensitivity index (ISI) and homeostasis model of assessment (HOMA), and systemic lipid peroxidation determined by plasma F2-isoprostane levels. A total of 74 subjects were randomized (33 phlebotomy and 41 control). The phlebotomy group underwent a median (range) of 7 (1-19) venesection sessions and had a significantly greater reduction in ferritin levels over 6 months, compared to controls (-148±114 vs. -38±89 ng/mL; P<0.001). At 6 months, there was no difference between phlebotomy and control groups in HS (17.7% vs. 15.5%; P=0.4), serum ALT (36 vs. 46 IU/L; P=0.4), or CK-18 levels (175 vs. 196 U/L; P=0.9). Similarly, there was no difference in end-of-study ISI (2.5 vs. 2.7; P=0.9), HOMA (3.2 vs. 3.2; P=0.6), or F2-isoprostane levels (1,332 vs. 1,190 pmmol/L; P=0.6) between phlebotomy and control groups. No differences in any endpoint were noted in patients with hyperferritinemia at baseline. Among patients undergoing phlebotomy, there was no correlation between number of phlebotomy sessions and change in HS, liver injury, or IR from baseline to end of study. Conclusion: Reduction in ferritin by phlebotomy does not improve liver enzymes, hepatic fat, or IR in subjects with NAFLD.